(3QSGdI GdZjHI (B( (3GdQSGdI GdJi hQOJ Ydi jO CHj jYdG(B)s
(3ChdgG (B:s
(3hgj QSGdI GdJMPjQ HYO GdZjHI HTghQ YOI hcGf GdNGU HgG Ggd LRjQI GdTGe s
(3BNQgG (B:s
(3acCfi Hce hbO CJGce efcQhf cKjQhf hjOYhf GdeHWdhf hgh MSHfG hHg fSJYjf ai LejY GdGehQ hgh GdeYjf hGdfUjQ JeJ hGdMeO dehdGfG hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B21s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3QSGdI ef QSGFd GdOQhR s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds